How Many Individuals with Asthma Need to Be Vaccinated to Prevent One Case of Invasive Pneumococcal Disease? - Julie M Okapuu; Estelle Chétrit; Brigitte Lefebvre; Caroline Quach (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The American Advisory Committee on Immunization Practices recommended the inclusion of adults with asthma in the high-risk category for pneumococcal vaccination based on a twofold increase in risk of invasive pneumococcal disease (IPD).